Constitutively active Stat5b in CD4(+) T cells inhibits graft-versus-host disease lethality associated with increased regulatory T-cell potency and decreased T effector cell responses - Vogtenhuber, Christine (American Society of Hematology, 2010)
Overexpression of a constitutively active form of Stat5b (Stat5b-CA) increases regulatory T cells (Tregs). We show that Stat5b-CA transgenic (TG) CD4(+) T cells had a markedly reduced graft-versus-host disease (GVHD) capacity versus wild-type (WT) T cells. Stat5b-CA TG versus WT CD4(+) T cells had a higher proportion of Tregs, which were superior in suppressing alloresponses mediated by CD4(+)CD25(−) effector T cells (Teffs). By day 5 after transplantation, Stat5b-CA TG Tregs had expanded approximately 3-fold more than WT Tregs. Purified Stat5b-CA TG Tregs added to WT CD4(+)CD25(−) Teffs were superior on a per-cell basis for inhibiting GVHD versus WT Tregs. Surprisingly, rigorously Treg-depleted Stat5b-CA TG versus WT CD4(+)CD25(−) Teffs caused less GVHD lethality associated with diminished Teff proinflammatory and increased Th2 anti-inflammatory cytokine responses. Reduced GVHD by Stat5b-CA TG versus WT Teffs could not be explained by conversion into Tregs in day 10 posttransplantation spleen or small intestine. In addition, Stat5b-CA TG Teffs retained a graft-versus-leukemia response. These results indicate a major role for Stat5 in Treg expansion and potency along with a lesser but significant role in Teff activation and suggest a strategy of pharmacologic Stat5b up-regulation as a means of decreasing GVHD while retaining a graft-versus-leukemia effect.